Technique for reducing the surgical porosity of small-diameter vascular grafts - E. A. Nemets; A. I. Khairullina; V. Yu. Belov; V. A. Surguchenko; V. N. Vasilets; V. I. Sevastianov; E. A. Volkova; Yu. B. Basok (Вестник трансплантологии и искусственных органов)
High surgical porosity (SP) is one of the causes of significant blood loss, as well as hematoma formation. So, reducing the SP of small-diameter vascular grafts (VGs) is a crucial task.The objective of this work was to develop a technology for the formation of polycaprolactone (PCL)-based small-diameter VGs with a bioactive coating with reduced SP.Materials and methods. Porous VGs with an inner diameter of 3 mm were fabricated by electrospinning from 5% PCL solution with addition of 5–30% gelatin (PCL/G) on an NANON-01A unit (MECC CO, Japan). Bioactive coating was applied by sequential incubation of VGs in solutions of bovine serum albumin, heparin and platelet lysate with fixation in a glutaric aldehyde solution. The surface structure and mechanical properties of the samples were investigated. Functional properties of the bioactive VGs were evaluated in relation to their interaction with cell cultures in vitro.Results. It was found that introduction of gelatin into the working solution reduces SP from 30.4 ± 1.5 mL/(cm2 ·min) to 2.8 ± 0.5 ml/(cm2 ·min). It was shown that at a PCL/gelatin ratio of 9 : 1, the outer and inner sides of the bioactive VGs samples are characterized by surface uniformity (no defects), mechanical properties close to blood vessels of the same diameter (Young’s modulus 6.7 ± 2.1 MPa, tensile strength 26.7 ± 4.9 N and elongation to break 423 ± 80%) and ability to support adhesion and proliferation of human umbilical vein endothelial cell line, EA.hy926.Conclusion. Introduction of 10% gelatin content (by the polymer weight) into PCL solution reduces the SP of small-diameter VGs, leads to uniformity in their inner and outer surface, improvement in their mechanical properties without reducing their ability to support adhesion and proliferation of vascular endothelial cells.